Internalisasi Nilai-Nilai Wudlu dalam Kacamata Kedokteran maupun Tasawuf - Nurafrizal, Alvin (Maliki Interdisciplinary Journal, 2024)
Wudhu is a purification ritual ordered in the Al-Qur'an, especially in Surah Al-Maidah verse 6. This activity not only has a physical dimension, but also a spiritual and psychological one. Through ablution, Muslims cleanse themselves of impurity and sin, which contributes to external and internal cleanliness. This process involves washing the parts of the body that are often involved in sinful acts, thereby helping to maintain the purity of the soul. Research shows that ablution can improve health by removing germs and improving personal hygiene. From a Sufistic perspective, ablution has deep wisdom related to cleansing the soul. In addition, ablution also provides time for reflection and concentration before carrying out worship, supporting the physical and spiritual well-being of Muslims. By understanding the meaning and benefits of ablution in depth, individuals can strengthen their relationship with Allah and improve the quality of their worship. A B S T R A K Wudhu adalah ritual bersuci yang diperintahkan dalam Al-Qur'an, khususnya dalam Surat Al-Maidah ayat 6. Aktivitas ini tidak hanya memiliki dimensi fisik, tetapi juga spiritual dan psikologis. Melalui wudhu, umat Islam membersihkan diri dari najis dan dosa, yang berkontribusi pada kebersihan lahiriah dan batiniah. Proses ini melibatkan pembasuhan anggota tubuh yang sering terlibat dalam perbuatan dosa, sehingga membantu menjaga kesucian jiwa. Penelitian menunjukkan bahwa wudhu dapat meningkatkan kesehatan dengan menghilangkan kuman dan meningkatkan kebersihan pribadi. Dalam perspektif tasawuf, wudhu memiliki hikmah mendalam yang berkaitan dengan pembersihan jiwa. Selain itu, wudhu juga memberikan waktu untuk refleksi dan konsentrasi sebelum melaksanakan ibadah, mendukung kesejahteraan fisik dan spiritual umat Islam. Dengan memahami makna dan manfaat wudhu secara mendalam, individu dapat memperkuat hubungan mereka dengan Allah serta meningkatkan kualitas ibadah mereka.